2019
DOI: 10.1097/brs.0000000000002295
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Versus Delayed Surgical Treatment of Lumbar Disc Herniation for Acute Motor Deficits

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…Differently, the improvement of preoperative motor deficits depends on various factors like the duration of symptoms and on BMI [26]: the obese patient group in our cohort experienced symptoms for a shorter period but needed the same amount of time to recover from motor deficits as non-obese patients. Therefore, the overall factor of time and its impact on short-term recovery may be neglected for young patients presenting with obesity.…”
Section: Discussionmentioning
confidence: 75%
“…Differently, the improvement of preoperative motor deficits depends on various factors like the duration of symptoms and on BMI [26]: the obese patient group in our cohort experienced symptoms for a shorter period but needed the same amount of time to recover from motor deficits as non-obese patients. Therefore, the overall factor of time and its impact on short-term recovery may be neglected for young patients presenting with obesity.…”
Section: Discussionmentioning
confidence: 75%
“…Sicher scheint, dass die operative Therapie (in einem Kollektiv mit 40 % Paresen) der konservativen Therapie überlegen ist [28], eine Vermeidung langer Symptomatik (Tage bis Monate) scheint weitere Vorteile [29] hinsichtlich der funktionellen Wiederherstellung zu bieten. Eine aktuelle retrospektiv vergleichende Studie, die vor allem schwere motorische Defizite einschloss, konnte einen Vorteil der frühzeitigen Nukleotomie (< 48 h) nachweisen [30] (LoE 2b).…”
Section: Mechanisch Instabile Wirbelsäulenfrakturenunclassified
“…13 Several studies have been conducted for the ideal timing in lumbar discectomy, however without consensus in their results. 6,[13][14][15][16] Generally, a minimum waiting time of 6 to 8 weeks has been established due to the high probability of spontaneous symptom resolution. 7,8,13 However, it is still unclear whether a longer time to surgery (TTS) also leads to worse outcomes, and -if so -whether there is an optimal maximum TTS for favorable patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…2,15,16 However, the reports often evaluate pre hoc defined TTS cutoffs, or do not take into account long-term patientreported outcome, or are based on retrospective data. 2,13,[15][16][17][18][19] A recent analysis indicated that delayed surgery is associated with a lower probability of improvement in leg pain at 1 year postoperatively and that a TTS cutoff of 24 weeks should be aimed for to maximize chances of symptomatic improvement. 18 However, this study focused solely on leg pain outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation